Efficacy of Two Stabilizers in Nanoemulsions with Whey Proteins and Thyme Essential Oil as Edible Coatings for Zucchini - Iulia Bleoanca; Andreea Lanciu; Livia Patrașcu; Alina Ceoromila; Daniela Borda (Membranes, 2022)
Edible coatings are important for horticulture crops preservation and reducing food waste. Application of edible coatings followed by low-temperature storage prolongs the storability, preserves quality, and decreases the overall postharvest losses. This study evaluated the efficacy of two nanoemulsions formulae containing thyme essential oil and whey proteins as coatings for zucchini, with the purpose of extending their shelf-life. The nanoemulsions were rheologically evaluated and the formula with guar and arabic gum mix stabilizer (S) showed a better capacity to restructure after strain compared to the formulae with Tween 20 (T). The S coating material had a better capacity to integrate nanoparticles compared to T. However, when applied on zucchini, T coating was more effective in reducing weight loss showing 16% weight loss compared to 21% in S, after 42 days. At the end of storage at 10 °C, the T-coated zucchini had better firmness (p < 0.05) compared with S and both coatings were superior to control (p < 0.05). POD (peroxidase) activity was high in peel at the end of storage when also CAT (catalase) showed a sudden increase. On the 42nd day of storage, the highest enzymes activity (CAT, POD, and APX (ascorbate peroxidase)) was present in the S-coated zucchini peel. The most abundant volatile in T coating was α-pinene and 4-carene in S. Sensory analysis showed that T coating delayed the appearance of senescence while S exhibited surface cracks.